1999
DOI: 10.1128/mcb.19.12.8052
|View full text |Cite
|
Sign up to set email alerts
|

Novel Membrane-Targeted ERK1 and ERK2 Chimeras Which Act as Dominant Negative, Isotype-Specific Mitogen-Activated Protein Kinase Inhibitors of Ras-Raf-Mediated Transcriptional Activation of c-fos in NIH 3T3 Cells

Abstract: Expression of constructs encoding fusion proteins of ERK1 and ERK2 containing a C-terminal farnesylation motif (CAAX) is predominantly localized at the cell membrane and was activated by coexpression of constitutively active Ha-RasL61 and epidermal growth factor. Both fusion proteins significantly inhibit the transcriptional activation of a c-fos-chloramphenicol acetyltransferase reporter induced by RasL61, constitutively active MEK1, or constitutively active RafBXB. The corresponding SAAX chimeras or overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 102 publications
0
37
0
Order By: Relevance
“…When dysregulated, this cascade plays a major role in various pathological conditions, particularly cancer (2). ERK1/2 is regulated in part by its subcellular localization (3). Recent work has shown that ERK localization within the cell may be controlled by phosphoprotein enriched in diabetes (PED, also known as PEA-15 [phosphoprotein enriched in astrocytes]), a small, death effector domaincontaining protein (4).…”
mentioning
confidence: 99%
“…When dysregulated, this cascade plays a major role in various pathological conditions, particularly cancer (2). ERK1/2 is regulated in part by its subcellular localization (3). Recent work has shown that ERK localization within the cell may be controlled by phosphoprotein enriched in diabetes (PED, also known as PEA-15 [phosphoprotein enriched in astrocytes]), a small, death effector domaincontaining protein (4).…”
mentioning
confidence: 99%
“…The p38/ERK2 constructs were gifts from Dr. Melanie Cobb (13). The HA-ERK1-CAAX-pEF and HA-ERK1-SAAX-pEF constructs were as described (15). Kinase-dead HA-ERK1(K71R)-CAAX-pEF was generated by using the QuikChange TM kit (Stratagene) using HA-ERK1-CAAX-pEF as template.…”
Section: Methodsmentioning
confidence: 99%
“…Two recent molecular constructs can localize ERK signaling to permit a cell engineering approach to control localization. ERK chimeras that express the Ras farnesylation sequence at their C terminus (ERK1-CAAX and ERK2-CAAX) and are membranebound sequester endogenous ERK at the plasma membrane (1) and provide for plasma membrane-localized signaling. A catalytically inactive cytoplasmic MAP kinase phosphatase, MKP-3/Pyst1, which binds and sequesters ERK in the cytoplasm, but does not affect its activity (2,30), provides for cytosolic ERK signaling.…”
Section: Figmentioning
confidence: 99%
“…A change in cell motility is just one of the many pleiotropic effects of signaling mediated by the epidermal growth factor receptor (EGFR), 1 and it has been suggested that such specific cellular responses are determined by the spatial targeting of downstream signaling events. This simple concept is complicated by the fact that EGFR-mediated cell motility requires signaling through the ubiquitous intracellular effector, ERK (4), which is present in both the cytoplasmic and nuclear compartments.…”
mentioning
confidence: 99%